Critical therapy! Parker, I (ed) (1999) Deconstructlng psychotherapy. London: Sage. ISBN 0-7619-5713 pbk. 194 pages. - Akhurst, Jacqui (PINS-Psychology in Society, 2026)
Psychotherapeutic practice in post-apartheid South Africa seems to have retreated back into the consulting room, focussing largely on individuals, and there appears to be little sign of the political critique which emerged from certain groups within the discipline prior to the 1994 elections. As a psychotherapist, I have felt growing concern that much current practice lacks a "critical edge" and is largely oblivious to the dynamic debate around integrating concern with social and political issues and practice which is gaining ground elsewhere. In a number of other parts of the world, psychotherapists are being challenged to broaden the scope of both their practice in their consulting rooms, as well as to engage more actively in more public debate in order to tackle the crucial influences of socio-economic and political issues on individual and group mental health (e.g. Samuels, 1993). Certain "schools" of psychotherapy are grappling with the incorporation of the philosophical and practical applications of ideas and concepts drawn from what is broadly termed postmodernism. It was therefore with anticipation that I tackled this book, hoping that it might provide some guidelines for considering and critiquing psychotherapy in South Africa.